Microscopic Investigationsof Silicification and Lignification Suggest Their Coexistence in Tracheary Phytoliths in Date Fruits (Phoenix dactylifera L.) - George, Navomy; Antony, Asha; Ramachandran, Tholkappiyan; Hamed, Fathalla; Kamal-Eldin, Afaf (Frontiers in Plant Science, 2020)
Date fruits are special representative of hard fruits and one of the richest sources of dietary silica and edible lignin, which are believed to have several health benefits. In this study, we used optical and scanning electron microscopy (SEM) to investigate the presence of associations between silicification and lignification in date fruits (Phoenix dactylifera, L.). Phloroglucinol staining was employed to observe lignification in date fruits, while silicification was studied by SEM of whole fruits and their acid digesta. This work revealed the presence of heterogeneity and complexity in the silica phytoliths and the lignified structures in date fruits. It was found that lignin exists independently of silica in the secondary cell walls of parenchymal and sclereid cells and that silica exists independently of lignin in the spheroid phytoliths that surround the sclereid cells. Interestingly, a small proportion of lignin and silica seemed to co-exist as partners in the spiral coils of the tracheid phytoliths.